Genome-wide association meta-analyses and fine-mapping elucidate pathways influencing albuminuria - Alexander Teumer (Nature Portfolio, 2019)
Urinary albumin-to-creatinine ratio (UCAR) is associated with various clinical outcomes such as kidney disease and cardiovascular disease. Here, the authors report genome-wide meta-analysis in over 500,000 individuals and find 68 UACR loci, followed by statistical fine-mapping, gene prioritization and experimental validation in flies.